Modelling of the rehydration process of dried broccoli (brassica oleracea l. var. italica) stems - Erdem, Irem (2022)
Broccoli (Brassica oleracea L. var. Italica) is associated with numerous health benefits, due to its high content in various nutritional compounds. The production of dried broccoli stems can be a good strategy to add value to a by-product of broccoli's industry. This product can be used for direct consumption, or in salads and soups after rehydration. This study aimed at assessing and modelling the rehydration kinetics of dried slices of broccoli stems with 1 mm thickness. Fresh broccoli stems were convective dried at 55°C and average air velocity of 1.22 m/s. Water rehydration of dried broccoli stems was carried out, until equilibrium moisture content, at six different temperatures (20-70°C). Samples water uptake and the rate of moisture absorption increased, respectively, with time and temperature. The equilibrium moisture content was slightly affected by temperature. The first order and Peleg empirical models described well the kinetics at each temperature. The temperature dependence of the rehydration rate presented and Arrhenius behaviour, with activation energy of 5.74±1.02 kJ/mol and rate at 55°C of 0.054±0.003 min-1. The Peleg rate and capacity constants presented a linear relationship with temperature. A Peleg distribution with linear temperature dependence was the best model to predict all experimental data.